Pareto chart‐enabled screening of influential factors in designing transfersomes. Issue 1 (3rd November 2022) - Modi, Chetna; Bharadia, Praful
Abstract: Methotrexate is the treatment of choice for rheumatoid arthritis, having significant side effects on oral administration, prompting researchers to consider transdermal administration. Transfersomes can overcome the challenges of transdermal administration of drugs because of their deformable nature, allowing for greater skin penetration than other formulations. However, due to an enormous number of product and process variables, the manufacturing of transfersomes proved a pain. The goal of the research study was to use a Plackett‐Burman design to evaluate an important product and process variables connected with the preparation of methotrexate transfersomes. The influence of six product and process variables on %entrapment efficiency and vesicle deformability was investigated and according to p ‐values, and the Pareto chart, the concentration of lipid, edge activator, and methotrexate were found critical variables influencing vesicle features having positive and negative effects on variables. In the future, experimental design may be used to optimize these critical parameters for further exploration in the development of methotrexate transfersomes.